Simultaneously boosting hydrogen production and ethanol upgrading using a highly-efficient hollow needle-like copper cobalt sulfide as a bifunctional electrocatalyst - Sheng, Shuang; Ye, Ke; Gao, Yinyi; Zhu, Kai; Yan, Jun; Wang, Guiling; Cao, Dianxue (Journal of colloid and interface science, 2021)
[Display omitted] Electrocatalytic water splitting used for generating clean and sustainable hydrogen (H2) can be very promising to address current energy shortage and associated environmental issues. However, this methodology is severely impeded by the tardy oxygen evolution reaction (OER). Hence, designing a preferable kinetics and thermodynamics oxidation reaction that supersede OER is very significant for the energy-saving production of H2. Herein, hollow needle-like copper cobalt sulfide was constructed on carbon cloth (CuCo2S4/CC) as a bifunctional electrocatalyst to accelerate H2 generation and simultaneously convert ethanol into value-added acetic acid. Thanks to the synergistic effect and unique structure of Cu and Co, CuCo2S4/CC displays superior catalytic activity and durability in ethanol oxidation reaction (EOR) with a low potential of 1.38 V vs. RHE (@10 mA cm−2). Meanwhile, it exhibits excellent hydrogen evolution reaction (HER) performance. The homemade CuCo2S4/CC//CuCo2S4/CC ethanol–water electrolyser only demands a voltage of 1.59 V to deliver 10 mA cm−2, 150 mV less than that used for ordinary water splitting. This shows that the ethanol–water electrolyser elaborated here holds encouraging potential in the energy-saving production of H2 and oxidation of ethanol into value-added acetic acid. This present work may open the way for the rational design of other electrocatalysts for efficient biomass oxidation reaction and relevant H2 production applications.